MENGGALI MAKNA KURIKULUM: PERSPEKTIF HISTORIS DAN KONTEMPORER DALAN PENDIDIKAN INDONESIA - Aini, fadhilah; Sapriya, Sapriya; Rahmat, Rahmat; Husna, Nurul (Universitas Tanjungpura, 2025)
The education curriculum in Indonesia has undergone eleven revisions since independence, which is often not matched by adequate preparedness of educators and education infrastructure. This research aims to explore the meaning of the curriculum in depth from historical and contemporary perspectives, as well as compare curricula from various periods to provide a comprehensive understanding. The research method used is a qualitative approach through literature study and content analysis of scientific journals, textbooks, official government documents, and other relevant articles and publications. The results show that the curriculum in Indonesia continues to develop and adapt to social and technological changes. The 1947 curriculum emphasized national values and life skills, the 1952 curriculum focused on the relevance of the material to daily life, while the subsequent curriculum continued to adapt to the times. Curriculum implementation faces various challenges, including disparities in the quality of education between urban and rural areas and teachers' lack of preparation for curriculum changes. This research highlights the importance of a curriculum that is relevant to the needs of society and technological developments so that graduates can compete at the global level. The curriculum should be able to shape students' characters and prepare them for future challenges, with an emphasis on character and competency development.